Injuries and Illnesses Across 10 Years of Canada Games Competitions: 2009 - 2019 - Nicole J Chimera; Danielle Merasty; Monica R Lininger (North American Sports Medicine Institute, 2022)
# Background The Canada Games are a national level competition held every two years alternating between Summer and Winter Games. Participation in elite level athletics, like the Canada Games, have an inherent risk of injury and illness. # Purpose To analyze the incidence and characteristics of injuries and illnesses during Canada Games competitions from 2009-2019 (primarily) and to understand sex differences in odds of musculoskeletal injury for Summer and Winter Canada Games athletes (secondarily). # Study Design Descriptive Epidemiology Study # Methods Using a retrospective cohort, data were abstracted from medical incident reports generated during Canada Games from 2009 - 2019. Data were coded for body part injured and injury type or illness system; injuries were also categorized as acute or chronic. # Results Across all 10 years of competition, 3160 injuries reported in 8710 male athletes and 3272 injuries reported in 8391 female athletes. Injury incidence was 362.8 and 389.9 and illness incidence was 47.8 and 64.5 per 1000 male and female athletes, respectively. Female athletes had a 1.12 (95% CI: 1.06; 1.19) greater odds of injury and 1.37 (95% CI: 1.20; 1.57) greater odds of illness compared to male athletes. Overall, injury (399.31 vs. 360.31; p \< 0.001) and illness (68.67 vs. 47.30; p \< 0.001) incidences were higher in Winter Games, compared to Summer Games, per 1000 athletes. When comparing male and female athletes participating in similar sports, sex specific differences exist in odds of both injury and illness. # Conclusions Male and female athletes competing in Canada Games competitions demonstrate differences in injury and illness incidence and odds of injury. This suggests a need to examine if additional modifiable risk factors may exist, which could contribute to prevention strategies to reduce injury and illness during Canada Games competition. # Level of Evidence 3